Advanced Hybrid Clustering and Routing Techniques for Enhanced Enegy Efficiency in Wireless Sensor Networks - Kiruba, M. Sweety; Rajesh, K. P. (Journal of Neonatal Surgery, 2025)
Wireless Sensor Networks (WSNs) are essential in various fields such as environmental monitoring, healthcare, and industrial automation. However, the constrained battery capacity of sensor nodes makes energy efficiency a critical challenge, requiring innovative solutions to extend network longevity. This paper introduces an innovative hybrid algorithm designed to improve efficiency and prolong the lifespan of the network. The proposed method combines advanced data organization and transmission strategies to optimize overall performance. Through extensive simulations and comparative analyses, the algorithm demonstrates significant improvements in network longevity, data accuracy, and reliability compared to traditional methods [1] [2].